Ship operations new risks, liabilities and technologies in the maritime sector - Soyer, Barış; Tettenborn, Andrew (Informa Law from Routledge, 2021)
Part 1- Emerging Legal Problems and Liabilities for Ship Operators Chapter 1- Sanctions and Money Laundering -- Associate Professor George LeloudasInstitute of International Shipping and Trade Law, Swansea UniversityChapter 2- Criminal Liability of Seafarers and Operators- Professor Henrik RingbomScandinavian Institute of Maritime Law, Oslo UniversityChapter 3- Cyber Problems- The Tort Liabilities That Can Be Incurred by Shipowners and Operators Due to Inadequate Cyber Security- Daniel Martin, Partner, HFW, LondonChapter 4- Cyber Risks and Insurance- Professor Barış Soyer, Director, Institute of International Shipping and Trade Law, Swansea UniversityChapter 5- Insolvency Difficulties -- Professor Andrew Tettenborn, Institute of International Shipping and Trade Law, Swansea UniversityChapter 6- Liability for Wrongful Arrest --
Keywords: Maritime law; LAW / Legal Profession; bisacsh; LAW / Legal Profession